Seed banks alter metacommunity diversity: The interactive effects of competition, dispersal and dormancy. (29th December 2021) - Wisnoski, Nathan I.; Shoemaker, Lauren G.
Abstract: Dispersal and dormancy are two common strategies allowing for species persistence and the maintenance of biodiversity in variable environments. However, theory and empirical tests of spatial diversity patterns tend to examine either mechanism in isolation. Here, we developed a stochastic, spatially explicit metacommunity model incorporating seed banks with varying germination and survival rates. We found that dormancy and dispersal had interactive, nonlinear effects on the maintenance and distribution of metacommunity diversity. Seed banks promoted local diversity when seed survival was high and maintained regional diversity through interactions with dispersal. The benefits of seed banks for regional diversity were largest when dispersal was high or intermediate, depending on whether local competition was equal or stabilising. Our study shows that classic predictions for how dispersal affects metacommunity diversity can be strongly influenced by dormancy. Together, these results emphasise the need to consider both temporal and spatial processes when predicting multi‐scale patterns of diversity. Abstract : Dispersal and dormancy can promote the maintenance of biodiversity in variable environments, but theory and empirical studies tend to examine them in isolation. Here, we develop a spatially explicit metacommunity model incorporating seed banks. We found that dormancy and dispersal had interactive, nonlinear effects on the maintenance and distribution of diversity, highlighting the need to consider both temporal and spatial processes when predicting multi‐scale patterns of diversity.